Proceedings of the 45th Annual Design Automation Conference 2008
DOI: 10.1145/1391469.1391566
|View full text |Cite
|
Sign up to set email alerts
|

Statistical diagnosis of unmodeled systematic timing effects

Abstract: Explaining the mismatch between predicted timing behavior from modeling and simulation, and the observed timing behavior measured on silicon chips can be very challenging. Given a list of potential sources, the mismatch can be the aggregate result caused by some of them both individually and collectively, resulting in a very large search space. Furthermore, observed data are always corrupted by some unknown statistical random noises. To overcome both challenges, this paper proposes a statistical diagnosis fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…The authors in [6], showed the superior capability of using the polynomial kernel to handle high-order timing effects due to combinations of occurrence-based features. For X,Y coordinates we can use the Gaussian kernel,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [6], showed the superior capability of using the polynomial kernel to handle high-order timing effects due to combinations of occurrence-based features. For X,Y coordinates we can use the Gaussian kernel,…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the two or all three should be ranked higher than X,Y. In the work [6], this is called a higher-order effect, where the effect depends on a combination of multiple features rather than just a feature individually. …”
Section: Systematic Intra-die Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many feature ranking methods [14][15][16]. In this work, we calculate an importance Sort NETS in descending order with the value of item; 7:…”
Section: E Feature Rankingmentioning
confidence: 99%
“…Model-based statistical diagnosis, which was proposed in [14] for speed-path analysis to identify systematic timing effects with design-silicon timing mismatch, can also be applied to volume diagnosis. The overview of the model-based volume diagnosis (MVD) method is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%